2013
DOI: 10.1590/s1984-29612013005000009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and isolation of Toxoplasma gondii in horses from Brazilian slaughterhouses

Abstract: This study aimed to investigate anti-Toxoplasma gondii antibodies and to isolate the parasite from the brains of horses processed at slaughterhouses in Brazil. We collected brain and blood samples from 398 horses of various ages, from six Brazilian states. Serum samples were evaluated by indirect fluorescent antibody test (IFAT cut-off titre ≥ 1:64), and brains were submitted to mouse bioassay. Among the 398 horses, positivity for T. gondii was identified in 46 (11.6%) by IFAT and in 14 (3.5%) by mouse bioassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…Previously reported prevalence values of T. gondii in slaughtered horses were 52.6% by mouse bioassay in Egypt [14], 25% by MAT in China [16], 15% by combination of IFAT and mouse bioassay in Brazil [15], and 6.9% by MAT [13] to 10% by Sabin-Feldman dye test [12] in USA.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previously reported prevalence values of T. gondii in slaughtered horses were 52.6% by mouse bioassay in Egypt [14], 25% by MAT in China [16], 15% by combination of IFAT and mouse bioassay in Brazil [15], and 6.9% by MAT [13] to 10% by Sabin-Feldman dye test [12] in USA.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the observed genotypes within muscle samples show that horses were exposed to infections with a mixed genotype (II/III) in addition to clonal lineages (I and II). In two previous genotyping studies carried out on isolates from equids in Brazil, T. gondii type I and the chicken genotype 163 (TgCkBr220) were reported in horses [15] and a donkey [29], respectively. Type I, II and III strains have different virulence phenotypes in mouse models, with type I strains being the most virulent, and Type II and Type III being avirulent [2].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Da mesma forma, no Brasil, estudos sorológicos apontam diferentes prevalências com variação entre 0% e 70% (Ishizuka et al 1975, Silva et al 1981, Larangeira et al 1985, Costa et al 1986, Braccini et al 1992, Barcelos et al 1997, Vidotto et al 1997, Gazêta et al 1997, Garcia et al 1999, Mendonça et al 2001, Naves et al 2005, Villalobos et al 2005, LocatelliDittrich et al 2006, Coiro et al 2012, Oliveira Filho et al 2012, Evers et al 2013, Oliveira et al 2013, Valença et al 2015.…”
Section: Introductionunclassified
“…Because domestic and feral cats are the natural de finitive host, they play an important role in disseminating of toxoplasmosis [1][2][3][4][5]. Rodents are very important reservoir in dissemination of toxoplasmosis in Iran.…”
Section: Introductionmentioning
confidence: 99%